Analisis Manajemen Risiko Pengelolaan Sumber Daya Manusia pada Pit-Stop Kopi Kig - Chodri; Rahmad Jumadi; Raden Achmad Djazuli (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to identify possible risks that arise related to human resource management and determine the level of impact of these risks on the Coffee Pit-Stop. Apart from that, this research is also intended to come up with suggestions for actions or efforts that can be made to minimize the risks that occur. The method used is a qualitative approach with descriptive data presentation and referring to the ISO 31000 standard guidelines. The research results identified five main risks, namely shortage of human resources, unclear responsibility and authority, low employee loyalty, inability to monitor employee performance, and a decline human resource competency. The main risk that must be addressed first is low employee loyalty by creating a positive and supportive work environment and offering career development opportunities. Other proposed actions include providing ongoing training and development programs, carrying out appropriate human resource planning, building effective communication between management and employees, and evaluating and reorganizing the organizational structure if necessary.